Effects of carbon availability in a woody carbon source on its nitrate removal behavior in solid-phase denitrification. (15th September 2019) - Hu, Rongting; Zheng, Xilai; Zheng, Tianyuan; Xin, Jia; Wang, Huan; Sun, Qiguo
Abstract: Woody biomass is the most common natural carbon source applied in solid-phase denitrification (SPD). However, its denitrification ability is low in the SPD process due to its poor carbon availability. In this study, sawdust samples were pretreated to various degrees, and then filled into SPD bioreactors to reveal the relationship between carbon availability and denitrification behaviors. The behaviors include the denitrification process, internal effects of major factors (carbon availability, pH and temperature), and the presence of bacterial communities. Results shown that the long-term denitrification rate of pretreated sawdust was increased by 4.5–4.8 times over that of untreated sawdust (29.3 mg N L −1 sawdust d −1 ). However, despite improving the pretreatment degree of the sawdust in the bioreactor, the long-term denitrification rate shown no further increase. The denitrification rate was most influenced by the temperature, followed by the pH, and then the sawdust pretreatment degree. The denitrification rate increased with decreasing pH and rising temperature of the pretreated sawdust. The removed nitrate was rarely converted into nitrite or nitrous oxide, but ammonium was produced at high pH and temperature for the pretreated sawdust. The adverse effects of ammonium and dissolved organic carbon (DOC) reduced when the pH of the pretreated sawdust was lowered to 6.5. Hydrolytic and denitrifying bacteria formed the main SPD bioreactor bacteria, whose abundances increased with increasing sawdust pretreatment degree. The results were beneficial to reduce the hydrolytic retention time and adverse products for the SPD system using woody carbon source. Graphical abstract: Image 1 Highlights: Nitrate removal rates increased by 4.5–4.8 times with pretreated sawdust. Bioreactors with pretreated sawdust maintained a high nitrate removal rate. Denitrification efficiency improved with lowering pH for pretreated sawdust. Functional bacteria abundances increased with rising sawdust pretreatment degree.